An Overview of Topical Immunomodulators used in Ophthalmology - Pranita Sahay; Devesh Kumawat (Delhi Journal of Ophthalmology)
Immunomodulators (IMT) are a novel class of drug that suppress the host immune response and inhibit the inflammatory cascade. They have several advantage over steroids when used for clinical conditions requiring long-term inflammation control. In the field of ophthalmology, IMT have been put to use for various indications like uveitis, dry eye disease, allergic eye disease, ocular surface tumours and other ocular surface disorders. It is also used intra-operatively in glaucoma surgeries, pterygium excision and photo-refractive keratectomy to increase the surgical success. The topical use of these drugs is relatively safe when compared to systemic use; hence, majority of the above conditions are treated with topical IMT. Cyclosporine A, Tacrolimus, Mitomycin C, 5-Fluorouracil and Interferon-alpha are some of the commonly used topical IMT in ophthalmic practice. Topical Lifitegrast is a recently approved drug with immunomodulatory mechanism of action that is used in management of refractory dry eye disease. In this review, we aim to provide the readers an overview of the pharmacology, clinical uses and adverse effects of these commonly used topical IMT.